PENGARUH TEAMS GAMES TOURNAMENT PADA PEMBELAJARAN PENDIDIKAN PANCASILA TERHADAP KECERDASAN EMSOIONAL SISWA KELAS IV SEKOLAH DASAR - Siti Nurkholifah; Otib Satibi Hidayat; Indah Wardatussa’idah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This experimental study aims to determine the effect of the Teams Games Tournament (TGT) model on the emotional intelligence of fourth-grade elementary school students in the subject of Pendidikan Pancasila. The research subjects consisted of two classes: Class IV A as the experimental class using the TGT model and Class IV B as the control class using the STAD model, with 30 students in each class. The emotional intelligence questionnaire was tested for validity and reliability through a trial involving. The post-test analysis showed a significant difference (Sig. 0.001 < 0.05) between the two groups, with the experimental class having a higher average score (93.73) compared to the control class (78.87). The implementation of the TGT model enhanced students’ empathy, self-control, and cooperation. The TGT model is recommended as an effective strategy for fostering emotional intelligence in Pancasila Education.